Using Song and Story-Telling in Mastering English Vocabulary for Elementary Students - La Ode Hampu (Scope : Journal of English Language Teaching, 2018)
The objective of this study is to investigate whether teaching using song or story-telling is more effective in mastering English vocabulary for elementary students. The method of this research is quasi experiment. The data is analyzed by using t-test. Based on the data analysis, the results show that there is significant difference of student’s vocabulary mastery those who are taught using song and those who are taught using story-telling. It was supported by the result of class experiment mean 79,83, median 80,83, modus 81, 83, standard deviation 7,30,  while the result of class control mean 69.50, median 74, 25, modus, 71,5 and standard deviation 7,21. Based on t-test show t counting= 5,620 and t table =2,002 with significance 5% or ( ) and dk=58 that it is meant t counting > t table (5,620 > 2,002) and Ho is rejected and H1 is accepted. In short, teaching using song on students mastering English vocabulary is more effective than using story-telling for the fourth grade students.  Key words: vocabulary, song, story-telling